Surrogate motherhood: the legal standing in Malaysia / Fariza Mohamad Nasir and Illy-Nadiah Mohd Yusof. - Nasir, Fariza Mohamad; Mohd Yusof, Illy-Nadiah (2007)
Surrogacy is the involvement of a voluntary third party for bearing another couple's child (ren) within her. This voluntariness could be awarded with some valuable consideration. From another point of view, this process could be seen as a transaction of human commodity that portrays the downfall of the human morality. However, from the other side, it is seen as a success to vast changing technologies that gives the human a total advantage and serves as the ultimate effort for those who are persistent in breeding their own child. Conflicts that arise are discussed throughout the chapters with references to countries such as USA and India for a balanced view between a liberal country and a country which has similar legislation to Malaysia. In addition, the required processes and a sample of the agreement between the parent and the surrogate mother is also included as a basis for a further research in order to find similarities that could be applied to the circumstances in Malaysia Some arguments and comments of the Malaysian legislation are also included. This opens up debates over the relevance of the procedure (surrogacy) with the existing law in the country. In furtherance to that, recommendations are given to fill in some of the lacuna that is found in the legislation in allowing this method of reproduction to be strictly applied to the non-Muslims only. Surrogacy is the involvement of a voluntary third party for bearing another couple's child (ren) within her. This voluntariness could be awarded with some valuable consideration. From another point of view, this process could be seen as a transaction of human commodity that portrays the downfall of the human morality. However, from the other side, it is seen as a success to vast changing technologies that gives the human a total advantage and serves as the ultimate effort for those who are persistent in breeding their own child. Conflicts that arise are discussed throughout the chapters with references to countries such as USA and India for a balanced view between a liberal country and a country which has similar legislation to Malaysia. In addition, the required processes and a sample of the agreement between the parent and the surrogate mother is also included as a basis for a further research in order to find similarities that could be applied to the circumstances in Malaysia. Some arguments and comments of the Malaysian legislation are also included. This opens up debates over the relevance of the procedure (surrogacy) with the existing law in the country. In furtherance to that, recommendations are given to fill in some of the lacuna that is found in the legislation in allowing this method of reproduction to be strictly applied to the non-Muslims only.